An Electrophysiological Study of Peripheral Polyneuropathy in Brucellosis - AKKOYUNLU, YASEMİN; BENBIR, Gulcin; TURSUN, Irfan; Akkoyunlu, YASEMİN; Kiziltan, Meral E. (My University, 2013)
Background: Brucellosis is an anthropozoonotic disease with heterogeneous clinical presentations. This study aims to investigate the peripheral nervous system (PNS) involvement in brucellosis.